The Incidence of Functional Disorders and Clinical Symptoms that May be Associated with Lactase Deficiency in Infants of Lviv - R.V. Tkach; S.L. Nyankovskyy; O.S. Nyankovska; M.S. Yatsula (Zaslavsky O.Yu., 2016)
Today, the violations of the digestive system in children of the first years of life remain the actual problem of practical pediatrics and are the common cause for parents to visit a doctor. The importance in the genesis of functional disorders of the digestive system in children of this age may belongs to lactase deficiency. 327 children from Lviv were included in the questionnaire survey. The aim of the study was to evaluate the incidence of clinical symptoms that may be associated with lactase deficiency in infants. Among the clinical symptoms in young children, according to the survey, regurgitation and colic, stool disorders dominated. The diagnosis of lactase deficiency was established in 3.4 % (11) of children, 2.8 % (9) children received enzyme of lactase.